2011
DOI: 10.1016/j.cmet.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

C2 Domain-Containing Phosphoprotein CDP138 Regulates GLUT4 Insertion into the Plasma Membrane

Abstract: Summary The protein kinase Bβ (Akt2) pathway is known to mediate insulin-stimulated glucose transport through increasing glucose transporter GLUT4 translocation from intracellular stores to the plasma membrane (PM). Combining quantitative phosphoproteomics with RNAi-based functional analyses, we show that a previously uncharacterized 138-kDa C2 domain-containing phosphoprotein (CDP138) is a substrate for Akt2, and is required for optimal insulin-stimulated glucose transport, GLUT4 translocation, and fusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…Indeed, there are reports that GLUT4 exocytosis requires intracellular Ca 2+ in adipocytes, allowing activation of Akt (Whitehead et al, 2001) and CDP138, a Ca 2+ -dependent protein downstream of Akt (Xie et al, 2011). In skeletal muscle, however, direct evidence showing intracellular Ca 2+ -dependent GLUT4 translocation was missing, although results have suggested that it occurs (Lanner et al, 2006;Wijesekara et al, 2006), and localized, sub-membrane changes in Ca 2+ levels have been reported in response to the hormone (Bruton et al, 1999).…”
Section: The Ros-ryr1 Branchmentioning
confidence: 77%
“…Indeed, there are reports that GLUT4 exocytosis requires intracellular Ca 2+ in adipocytes, allowing activation of Akt (Whitehead et al, 2001) and CDP138, a Ca 2+ -dependent protein downstream of Akt (Xie et al, 2011). In skeletal muscle, however, direct evidence showing intracellular Ca 2+ -dependent GLUT4 translocation was missing, although results have suggested that it occurs (Lanner et al, 2006;Wijesekara et al, 2006), and localized, sub-membrane changes in Ca 2+ levels have been reported in response to the hormone (Bruton et al, 1999).…”
Section: The Ros-ryr1 Branchmentioning
confidence: 77%
“…Recently, it has been reported in live adipocytes that the 138-kDa C2 domain-containing phosphoprotein (CDP138) is required for optimal insulin-stimulated glucose transport, GLUT4 translocation, and fusion of GLUT4-containing vesicles with the plasma membrane (63). The purified C2 domain of CDP138 binds Ca 2ϩ and lipid membranes (63).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported in live adipocytes that the 138-kDa C2 domain-containing phosphoprotein (CDP138) is required for optimal insulin-stimulated glucose transport, GLUT4 translocation, and fusion of GLUT4-containing vesicles with the plasma membrane (63). The purified C2 domain of CDP138 binds Ca 2ϩ and lipid membranes (63). In addition, studies in vitro have shown that the cytoplasmic protein Doc2b, which possesses two homologous C2 domains, promotes GLUT4 exocytosis by activating the SNARE-mediated fusion reaction in a calcium-and membrane-bending-dependent manner (65).…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular Fractionation with Continuous Iodixanol Gradients-Subcellular fractionation was performed using a method as previously reported (24,25). In short, the cells were washed with cold PBS and homogenized in buffer (20 mM Hepes, pH 7.4, 1 mM EDTA, 250 mM sucrose with protease and phosphatase inhibitors) 20 times with a 22-gauge needle and 5 times with a 26 gauge needle.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous reports (24,25), the lower density fractions mainly contains plasma membrane, whereas the middle density fractions contain large organelles including Golgi apparatus and the higher density fractions mainly consist of small organelles including endosomal structures. When caT␤RI was expressed alone, it was mainly distributed in the fractions containing large subcellular organelles (Fig.…”
Section: Tollip Interacts With Ubiquitinated Tgf-␤ Type I Receptor Thmentioning
confidence: 99%